Development and verification of dynamic electromagnetic model of asynchronous motor operating in terms of poor-quality electric power - Tryputen, M.; Kuznetsova, A.; Tryputen, M. (НТУ ДП, 2021)
Several approaches are known which help take into consideration parameters of supply voltage while modeling processes in electromechanical systems. In terms of nonsinusoidality of supply voltage in classic variant, its spectrum analysis is performed; then, the required equations are represented for each harmonic taking into account its amplitude and phase. Those equations are solved either analytically or numerically; the necessary value is found as a geometrical total of all the harmonic constituents.
Keywords: electromagnetic model; development